Religious Moderation, Inclusive, and Global Citizenship as New Directions for Islamic Religious Education in Madrasah - Mirzon Daheri (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article examines the direction of the development of Islamic religious education in Madrasah. The main subject of the research is the Decree of the Minister of Religion (KMA) number 183 of 2019 concerning the Islamic religious education curriculum and Arabic language in Madrasah. This research is very important in order to be able to explore the direction of the development of Islamic Religious Education in Madrasah and how to determine the basis for that direction. This clarity can ensure the truth or untruth of various issues milling about this, one of which is the issue of the abolition of Islamic religious education lessons. Researchers studied with a descriptive qualitative approach using content analysis techniques. So far, no researcher has studied this subject. The results show that the direction of Islamic religious education was born through in-depth study. Development is based on philosophical, sociological, psycho-pedagogical, and theoretical foundations as well as a rationalization so that it can be said to be a systemic and measurable reinforcement. Moderate and inclusive behavior is one of the goals that is strengthened as the direction of Islamic religious education in Madrasah so students are ready dan play positif as global citizenship.